THE CORRUPTION TRENDS WITHIN THE ASEAN COUNTRIES: A BIBLIOMETRIC ANALYSIS REVIEW - Muliani, Muliani; Sayuti, Alfian; Septian, Defel (STIE Pelita Nusantara Semarang, 2024)
This article gives a quantitative examination of corruption trends in one of the ASEAN countries. The study focused on 5 research questions. Information is collected to check the above research questions and a network map is applied. This study aims to examine the publication of documents based on the most influential articles, co-authorship of country, co-occurrenceance of all keywords, most cited sources, co-citation of cite author. Keywords are categorized into several clusters. The type of analysis used is bibliometric analysis. This study took the latest data of 823 articles from the scientific database, namely SCOPUS from 2000-2024, and network analysis using VOSviewer software. This study found that The most influential article in the study of Corruption in ASEAN Country is the article entitled